Monitoring of WT1 expression in PB and CD34(+) donor chimerism of BM predicts early relapse in AML and MDS patients after hematopoietic cell transplantation with reduced-intensity conditioning - Lange, T.; Hubmann, M.; Burkhardt, Ralph; Franke, G-N; Cross, M.; Scholz, Markus; Leiblein, S.; Al-Ali, H. K.; Edelmann, J.; Thiery, Joachim; Niederwieser, D. (Leukemia, 2011)
Relapse of malignant disease remains the major complication in patients with acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS) after hematopoietic cell transplantation (HCT) with reduced-intensity conditioning (RIC). In this study, we investigated the predictive value of disease-specific markers (DSMs), donor chimerism (DC) analysis of unsorted (UDC) or CD34(+) sorted cells and Wilms’ tumor gene 1 (WT1) expression. Eighty-eight patients with AML or MDS were monitored after allogenic HCT following 2 Gy total-body irradiation with (n=84) or without (n=4) fludarabine 3 × 30 mg/m(2), followed by cyclosporin A and mycophenolate mofetil. DSMs were determined by fluorescence in situ hybridization (FISH) and WT1 expression by real-time polymerase chain reaction. Chimerism analysis was performed on unsorted or CD34(+) sorted cells, by FISH or short tandem repeat polymerase chain reaction. Twenty-one (24%) patients relapsed within 4 months after HCT. UDC, CD34(+) DC and WT1 expression were each significant predictors of relapse with sensitivities ranging from 53 to 79% and specificities of 82-91%. Relapse within 28 days was excluded almost entirely on the basis of WT1 expression combined with CD34(+) DC kinetics. Monitoring of WT1 expression and CD34(+) DC predict relapse of AML and MDS after RIC-HCT.